A meta-analysis of the technical efficiency of yam production in Nigeria. Issue 1 (2nd January 2021) - Morse, Stephen
ABSTRACT: The paper presents the first meta-analysis of yam ( Dioscorea rotundata Poir) production studies in Nigeria, with a special emphasis on technical efficiency. The focus was on published studies in journal papers and conferences. For the meta-analysis of production function, a total of 40 studies were included for ware yam and 3 for seed yam, for technical efficiency a total of 23 ware yam and 3 seed yam studies were included and for the farm budget meta-analysis, a total of 22 ware yam and 6 seed yam studies were included. The "peak" years of publication of the ware yam studies were from 2012 to 2014. The bulk of the studies took place in the major yam-growing states, such as Ekiti, Benue, and Kogi. Technical efficiency of yam production varied between and within each of the studies, with an average technical efficiency across studies of between 0.6 and 0.8. The studies highlight the importance of knowledge; it is not just about the quantity of inputs applied but how they are used that matters. The paper notes that meta-analyses of studies designed to explore the factors influencing production of agricultural crops in Nigeria are relatively sparse in number, yet given the importance of agriculture in the country, both for the livelihoods of millions of people, and export, then more such analyses are needed.